Eruptions at Lone Star geyser, Yellowstone National Park, USA: 2. Constraints on subsurface dynamics. Issue 12 (5th December 2014) - Vandemeulebrouck, Jean; Sohn, Robert A.; Rudolph, Maxwell L.; Hurwitz, Shaul; Manga, Michael; Johnston, Malcolm J. S.; Soule, S. Adam; McPhee, Darcy; Glen, Jonathan M. G.; Karlstrom, Leif; Murphy, Fred
Abstract We use seismic, tilt, lidar, thermal, and gravity data from 32 consecutive eruption cycles of Lone Star geyser in Yellowstone National Park to identify key subsurface processes throughout the geyser's eruption cycle. Previously, we described measurements and analyses associated with the geyser's erupting jet dynamics. Here we show that seismicity is dominated by hydrothermal tremor (~5–40 Hz) attributed to the nucleation and/or collapse of vapor bubbles. Water discharge during eruption preplay triggers high‐amplitude tremor pulses from a back azimuth aligned with the geyser cone, but during the rest of the eruption cycle it is shifted to the east‐northeast. Moreover, ~4 min period ground surface displacements recur every 26 ± 8 min and are uncorrelated with the eruption cycle. Based on these observations, we conclude that (1) the dynamical behavior of the geyser is controlled by the thermo‐mechanical coupling between the geyser conduit and a laterally offset reservoir periodically filled with a highly compressible two‐phase mixture, (2) liquid and steam slugs periodically ascend into the shallow crust near the geyser system inducing detectable deformation, (3) eruptions occur when the pressure decrease associated with overflow from geyser conduit during preplay triggers an unstable feedback between vapor generation (cavitation) and mass discharge, and (4) flow choking at a constriction in the conduit arrests the runaway process and increases the saturated vapor pressure in the reservoir by a factor of ~10 during eruptions.